Sideways Developments - Cheang, Kai Hang (Michigan State University Press, 2026)
Sideways Developments examines Hong Kong Anglophone and Cantophone literature and visual culture to trace the forms of queer and trans survival and flourishing in the Asian century. Contesting the cisgender, heterosexual, linear tropes that constitute developmentalist narratives deployed by superpowers—from colonial Britain to 20th-century America to a rising China—Cheang argues that sideways aesthetics define the narratives through which the LGBTQ+ community navigates personal and socioeconomic transitions. Through formalist analyses of a range of genres, Cheang reveals the affordances of queer and trans cultures for addressing the question of Hong Kong during its period of promised transition until 2047. In this moment of multiple crises, Sideways Developments offers a timely hermeneutic and theory of solidarity and sustainability. The book tracks how sideways aesthetics have evolved from a feature of LGBTQ+ plots, performance, and nonlinear approaches to space-time to a form of togetherness that links postcolonial Hong Kong with struggles worldwide. Using what Cheang terms intersectional formalism as an analytical tool, the book provides a multilayered examination of the alternative pathways exemplified by queer and trans resilience and regeneration.